Role of quantum chemical calculations in molecular biophysics with a historical perspective - Kukushkin, A.; Jalkanen, Karl (Springer Berlin, 2009)
We discuss how the basic principles of quantum chemistry and quantum mechanics can be and have been applied to a variety of problems in molecular biophysics. First, the historical development of quantum concepts in biophysics is discussed. Next, we describe a series of interesting applications of quantum chemical methods for studying biologically active molecules, molecular structures, and some of the important processes which play a role in living organisms. We discuss the application of quantum chemistry to such processes as energy storage and transformation, and the transmission of genetic information. Quantum chemical approaches are essential to comprehend and understand the molecular nature of these processes. To conclude our work, we present a short discussion of the perspectives of quantum chemical methods in modern biophysics, the field of experimental and theoretical chiral vibrational and electronic spectroscopy.